Perbedaan Efektivitas Aktivitas Jogging dan Senam Aerobik Terhadap Kadar Gula Darah Sewaktu Pria Remaja - Grido Handoko Sriyono; Nur Hamim; Umi Narsih (Jurnal Health Sains, 2023)
Running and gymnastics have a very important role for burning calories, where running will consume energy (burning calories) and reduce body fat so that it can increase the ability of cell metabolism to absorb and store glucose. The benefits of exercise for diabetics include increasing blood glucose levels, prevent obesity, play a role in overcoming the possibility of atherogenic complications. The purpose of this study was to determine the effectiveness of running and gymnastics activities on blood sugar levels when in adult men divided into two sample groups, each of them was 10 people for running sports activities and 10 people for gymnastic activities. The design of this study was experimental using a sample of 20 adult men. The independent variable in this study is the activity of jogging running and aerobic exercise and the dependent variable of this study is blood sugar levels in adult men. The measuring instrument used to determine blood sugar levels during this study was GCU Nesco multicheck. Independent t statistic test obtained the value of sig. (2-tailed) <0.05 which shows there is a significant difference between running and gymnastics to reduce blood sugar levels. The results of this study conclude that jogging running is more effective than aerobic exercise to reduce blood sugar levels in adult men.